HOW DOES CORRUPTION AFFECTS HEALTHCARE SECTOR IN BULGARIA - Jordan Deliversky (Peytchinski Publishing, 2016)
Corruption in the healthcare sector is a reflection of the structural challenges in the health care system. The problem of corruption in healthcare is of a multidimensional nature. The Bulgarian health care system is based on a regulated regime. On one hand there is the functioning of a state-owned and state-controlled health fund financed through obligatory contributions by all income earners, and on the other, a union of health providers that negotiate a national framework health contract with the fund. Causes of corruption are classified as different factors such as structural factors and government policies factors. The health sector is susceptible to corruption for various reasons, mostly related to its organization. The health sector is a complex sector. In order to be effective, reforms to combat corruption must be informed by theory, guided by evidence and adapted to context. It is necessary to review and develop diagnostic and treatment algorithms as standards of good medical practice, which would help to assess the package of medical and non-medical activities.